Demolished waste into an innovative resource for sand replacement in concrete (the dwarf technique)/ Muhammad Naim Mahyuddin ... [et al.] - Mahyuddin, Muhammad Naim; Azahari, Qalleesya Korish; Abd Rashid, Mohd Najib; Ismail, Sallehan (Universiti Teknologi MARA, Perak, 2024)
The construction sector generates substantial waste, including demolished concrete, presenting environmental challenges and disposal expenses. This study introduces the DWARF (Demolished Waste as Resource for Sand in Concrete) technique, an innovative method that repurposes demolished waste as a valuable resource for replacing sand in concrete production. The DWARF process involves treating the demolished waste to meet specifications for sustainable use as an alternative to natural sand in concrete mixes. This research investigated the feasibility and effectiveness of the DWARF technique concerning its impact on concrete's mechanical properties and sustainability. Experimental tests evaluated the compressive strength, durability, and environmental performance of concrete mixes with varying percentages of demolished waste as a sand replacement. The results were compared with conventional concrete mixes to assess the DWARF technique's performance. The findings indicated the successful incorporation of demolished waste into concrete mixes using the DWARF technique, resulting in comparable or improved mechanical properties compared to conventional concrete and additionally, using demolished waste as a sand replacement reduces the environmental impact associated with sand mining and waste disposal. The DWARF technique supports.